Cook-a-doodle-doo! - Stevens, Janet; Crummel, Susan Stevens (San Diego : Harcourt Brace, 1999)
With the questionable help of his friends, Big Brown Rooster manages to bake a strawberry shortcake which would have pleased his great-grandmother, Little Red Hen.
Keywords: Cake -- Fiction; Baking -- Fiction; Roosters -- Fiction; Animals -- Fiction